Devulcanization of styrene butadiene rubber by microwave energy: Effect of the presence of ionic liquid - S. Seghar; N. Ait Hocine; V. Mittal; S. Azem; F. Al-Zohbi; B. Schmaltz; N. Poirot (eXPRESS Polymer Letters)
In this study, styrene butadiene rubber (SBR) was devulcanized using microwave irradiation. In particular, effect of ionic liquid (IL), pyrrolidinium hydrogen sulfate [Pyrr][HSO4], on the devulcanization performance was studied. It was observed that the evolution of the temperature reached by rubber powder exposed to microwave irradiation for different energy values was favored by the presence of ionic liquid [Pyrr][HSO4] significantly over the whole range of the microwave energy values. Beyond the threshold point of 220 Wh/kg, the soluble fraction after devulcanization sharply increased with increasing devulcanization microwave energy. For the powder mixed with [Pyrr][HSO4], the increase was more significant. Furthermore, the crosslink density was observed to decrease slowly with the microwave energy up to 220 Wh/kg, beyond which the crosslink density decreased significantly for the rubber impregnated with IL. For the rubber with IL, significant and continuous increase in Tg with microwave energy values was observed in comparison with the SBR where no change in transition temperature was observed. Mechanical shearing of rubber gums in the two-roll mill favored the devulcanization process, which indicated that the combination of mechanical loading with microwave energy and IL is an efficient procedure allowing an optimal devulcanization of rubbers.